2006
DOI: 10.4049/jimmunol.176.11.6690
|View full text |Cite
|
Sign up to set email alerts
|

Degeneracy and Repertoire of the Human HIV-1 Gag p1777–85 CTL Response

Abstract: CD8+ CTL responses are important for the control of HIV-1 infection. The immunodominant HLA-A2-restricted Gag epitope, SLYNTVATL (SL9), is considered to be a poor immunogen because reactivity to it is rare in acute infection despite its paradoxical dominance in patients with chronic infection. We have previously reported SL9 to be a help-independent epitope in that it primes highly activated CTLs ex vivo from CD8+ T cells of seronegative healthy donors. These CTLs produce sufficient cytokines for extended auto… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
26
0

Year Published

2006
2006
2016
2016

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 27 publications
(26 citation statements)
references
References 62 publications
0
26
0
Order By: Relevance
“…However, it is important that sequence selection is based on a comprehensive approach that will enable the identification of optimal antigens, either alone or in combination, for incorporation into vaccines delivered in the setting of both host and viral heterogeneity. 51 In conclusion, we have shown that minor genetic differences in viral epitopes and host restriction elements can dramatically affect CD8 T-cell immunity with profound implications for the biologic outcome of HIV infection. These findings indicate that, in addition to the identification of optimal antigens, rational vaccine design should also incorporate a comprehensive approach to epitope sequence selection guided by detailed analyses of the downstream consequences of immunization.…”
Section: Discussionmentioning
confidence: 79%
“…However, it is important that sequence selection is based on a comprehensive approach that will enable the identification of optimal antigens, either alone or in combination, for incorporation into vaccines delivered in the setting of both host and viral heterogeneity. 51 In conclusion, we have shown that minor genetic differences in viral epitopes and host restriction elements can dramatically affect CD8 T-cell immunity with profound implications for the biologic outcome of HIV infection. These findings indicate that, in addition to the identification of optimal antigens, rational vaccine design should also incorporate a comprehensive approach to epitope sequence selection guided by detailed analyses of the downstream consequences of immunization.…”
Section: Discussionmentioning
confidence: 79%
“…Landay noted the importance of microbial translocation in immune activation through the TLR-4 pathway and in inducing proinflammatory cytokines. 49 He suggested the possibility of a common pathway of the proinflammatory cytokines driving immune activation characterized by HLA-DR and CD38 coexpressed on CD4 and CD8 T cells.…”
Section: Biomarkers For Immune Activationmentioning
confidence: 99%
“…HLA typing was possible for 280 of these samples, of which 121 were HLA-A2 ϩ . OLP21 (PRTLNAWVKVVEEKAP, p24 [17][18][19][20][21][22][23][24][25][26][27][28][29][30][31][32] ) was recognized by 24 subjects, with most of this reactivity (14 of 24) likely directed against the HLA-B*1503-restricted VKV VEEKAF epitope frequently seen in HLA-B*1503-expressing subjects (21). Reactivity to the nonameric TV9 peptide was confirmed in one of two HLA-A2 ϩ HLA-B*1503 Ϫ samples tested that reacted to OLP21 (L8 47, 500 sfc/10 6 PBMCs; Fig.…”
Section: Tv9 Reactivity In Hiv-1-infected Subjectsmentioning
confidence: 99%
“…Positively selected CD8 ϩ T cells (Dynabeads; Dynal Biotech) were primed with irradiated (4000 cGy) peptidepulsed or transduced DCs at a T cell-DC ratio of 5:1 in 48-well or 96-well cluster plates. Cells were cultured in complete medium containing 10 ng/ml IL-7 (Genzyme) and restimulated every 7-10 days with autologous monocytes pulsed with peptides or transduced DCs (24,25). IL-2 (20 U/ml) was added 1 and 4 days poststimulation.…”
Section: Healthy Seronegative Donorsmentioning
confidence: 99%
See 1 more Smart Citation